Association of anemia and cognitive impairment in patients undergoing maintenance hemodialysis: a cross-sectional study - Lin Huang; Yan Zhang; Jinbao Wang; Hongjin Tang; Jiajun Zhou (BMC Nephrology)
Abstract Background Cognitive impairment (CI) is common among end-stage renal disease (ESRD) patients undergoing maintenance hemodialysis (MHD), yet its relationship with hemoglobin levels remains underexplored. This study aimed to investigate the association between hemoglobin levels and CI in MHD patients, as well as to identify other contributing factors. Methods A cross-sectional study was conducted with 248 MHD patients (49.60% male, mean age 57.23 ± 13.16 years) from a single hemodialysis center. Cognitive function was assessed using the Mini-Mental State Examination (MMSE) with CI defined as a score < 24. Hemoglobin levels were divided into quartiles (Q1: < 90 g/L; Q2: 90–110 g/L; Q3: 110–130 g/L; Q4: >130 g/L). Various independent variables, including age, sex, education level, dialysis duration, comorbidities, and laboratory parameters were analyzed using Spearman correlation test, and univariate and multivariate regression. Results Of the 248 patients, 33.90% (84 patients) had CI. Higher hemoglobin quartiles (Q3/Q4) were associated with better cognitive function (higher MMSE scores, P < 0.001) and improved performance across cognitive domains. The Spearman and logistic regression analyses revealed the potential associations between cognitive function (MMSE scores) and several factors, including age, education level, dialysis duration, comorbidities, pre-dialysis blood pressure, interdialytic hypotension, albumin, creatinine, uric acid, and hemoglobin (P < 0.05). Age (OR = 1.454, P < 0.001), male sex (OR = 0.171, P = 0.013), pre-dialysis diastolic blood pressure (OR = 0.884, P = 0.024), and uric acid (OR = 0.992, P = 0.007) were significantly linked with the presence of CI in MHD patients. Multivariate regression further confirmed that adequate hemoglobin concentration was an independent related factor against CI in MHD patients (Model 4, Q1 vs. Q3: OR = 15.395, 95% CI = 3.184–74.443, P < 0.001). Conclusions Anemia is significantly associated with CI in MHD patients, and can still serve as a clinical marker for early detection and intervention in CI. Maintaining adequate hemoglobin levels may be linked with a reduced CI occurrence in hemodialysis patients. These findings highlight the importance of anemia management and tailored interventions to preserve cognitive function health in ESRD patients. Clinical trial number Not applicable.